Synthesis and biological evaluation of Aspergillomarasmine A derivatives as novel NDM-1 inhibitor to overcome antibiotics resistance. Issue 19 (1st October 2017) - Zhang, Jian; Wang, Sanshan; Wei, Qi; Guo, Qianqian; Bai, Yingjie; Yang, Shaoqiang; Song, Fuhang; Zhang, Lixin; Lei, Xiaoguang
Graphical abstract: Abstract: The β-lactam antibiotic resistance of Gram-negative bacteria has shown to be a critical global health problem. One of the primary reasons for the drug resistance is the existence of β-lactamases especially metallo-β-lactamases such as New Delhi metallo-β-lactamase (NDM-1) and Verona Integron-encoded metallo-β-lactamase (VIM-2). The fungal natural product Aspergillomarasmine A (AMA) has proven to be a promising inhibitor of NDM-1 and VIM-2 both in vitro and in vivo . Seven new analogues of AMA were synthesized by utilizing different strategies. The biological evaluation of these analogues was performed to study the structure-activity relationship of AMA both in vitro and in vivo . Remarkably, the lead compound 4 showed synergistic effect in combination with Meropenem to overcome the antibiotic resistance of the Gram-negative bacteria such as K. pneumoniae ( BAA-2146 ) expressing NDM-1.